3D fabrication of Shape-Memory polymer networks based on coumarin Photo-Dimerization. (5th October 2022) - Tarek Benkhaled, Belkacem; Belkhir, Kedafi; Brossier, Thomas; Chatard, Camille; Graillot, Alain; Lonetti, Barbara; Mingotaud, Anne-Françoise; Catrouillet, Sylvain; Blanquer, Sébastien; Lapinte, Vincent
Graphical abstract: Highlights: Transparent films based on photo-crosslinkable polymers bearing coumarin chromophore. Thermal-induced shape memory properties in unfolding and twisting deformations. Photoprintable resins for stereolithography. 4D printing resulting from additive fabrication of shape memory materials. Abstract: Photo-crosslinked shape-memory polymer (SMP) materials were obtained by the copolymerization of methacrylates bearing 2-ethylhexyl plasticizing group (EHMA) and photoactive coumarin unit (CoumMA). The photo-dimerization of coumarin units ensured the crosslinking of P(EHMA- co -CoumMA) and further allowed the fabrication by stereolithography of well-defined butterfly with ribbed wings to illustrate the potential of promising coumarin chemistry in additive fabrication. The influence of dye ratio on the optical and the mechanical properties of the transparent P(EHMA- co -CoumMA) films as well as the shape memory properties of the films in unfolding and twisting deformations were detailed and demonstrate the opportunity of coumarin-bearing photoprintable polymers for 4D printing.